Propagation of Partially Coherent Flat-Topped Vortex Hollow Beams in Anisotropic Turbulent Plasma - Abdu A. Alkelly; M. A. H. Khaled; Labiba F. Hassan (International Journal of Optics)
The propagation properties of partially coherent circular flat-topped (FT) vortex hollow/nonvortex beams are studied in anisotropic turbulent plasma. The analytical expression of the optical intensity of these beams is obtained by employing the extended Huygens–Fresnel integral. The effects of the source and turbulent plasma parameters on the intensity distribution of partially coherent circular FT vortex hollow/nonvortex beams are analyzed numerically. The results show that partially coherent circular FT vortex hollow/nonvortex beams will finally converge into a Gaussian intensity profile at increasing propagation distances. The results also showed that the partially coherent FT vortex hollow/nonvortex beams with higher coherence are less affected by anisotropic turbulent plasma than the less coherent beams.